Sick notes, general practitioners, emergency departments and fracture clinics. Issue 1 (20th December 2006) - Walker, C A; Gregori, A; O'Connor, P; Jaques, K; Joseph, R
Abstract : Background: General practitioner waiting times are increasing. The two national surveys regarding general practice showed that the number of patients waiting for ⩾2 days for an appointment rose from 63% to 72% between 1998 and 2002, with 25% waiting for ⩾4 days. The Department of Health recognised that many patients discharged from hospitals and outpatient clinics required to visit their general practitioner for the sole purpose of obtaining a sick note. The report entitled Making a difference: reducing general practitioner paperwork estimated that 518 000 appointments (and 42 000 GP h) could be saved by ensuring that these patients were issued with a sick note directly from hospital rather than being referred to their general practitioner. This practice was to be adopted from July 2001 and included patients discharged from wards as well as those seen in outpatient departments. Method: 50 emergency departments and fracture clinics in Scotland and England were contacted to assess whether these guidelines had been adopted. Only hospitals with both accident and emergency and fracture clinics were included; nurse-led and paediatric departments were excluded. Results: Of the 25 Scottish emergency hospitals contacted, 4 (16%) accident and emergency departments and 8 (32%) fracture clinics issued sick notes. This was compared with 5 of 25 (20%) accident and emergency departments and 12 of 25 (48%) fracture clinics in England. Four Scottish and five English accident and emergency departments stated that it was policy to give sick notes, three Scottish and four English departments said that it was policy not to give them and the rest (72% in Scotland and 64% in England) stated that they had no clear policy but "just don't give them". Conclusion: The 2001 guidance from the joint Cabinet Office/Department of Health has not been fully incorporated into standard practice in Scotland and England. If all emergency departments and fracture clinics were to issue sick notes to patients requiring >7 days absence from work, this could reduce general practitioner consultations and improve waiting times.